Addition of ketamine or dexmedetomidine to lignocaine in intravenous regional anesthesia: A randomized controlled study - Alok Kumar; D K Sharma; Barun Datta (Wolters Kluwer Medknow Publications, 2012)
Introduction: Ketamine and dexmedetomidine decrease anesthetic requirement and provide analgesia to patients. We designed this study to compare the effect of dexmedetomidine and ketamine when added to lignocaine in intravenous regional anesthesia (IVRA). Materials and Methods: Seventy two patients undergoing hand surgery were randomly assigned to three groups to receive IVRA. They received 20 ml of 1% lignocaine and either 1 ml of isotonic saline (Group L, n = 24); or 0.5 mg/kg body weight ketamine (Group LK, n = 24) or 1 mcg/kg body weight dexmedetomidine (Group LD, n = 24). Sensory and motor block onset and recovery time were noted. After the tourniquet deflation, pain and sedation values, time to first analgesic requirement and any side effects were noted. Results: Shortened sensory and motor block onset times (69.17 min and 7.83 min respectively, P < 0.0001) and improved quality of anesthesia (satisfaction score = 3, P < 0.05) were found in ketamine group. Visual analog scale scores (3.21 ± 0.41) were comparable while time to first analgesic requirement (166.25 ± 25.89 min, P < 0.0001) was significantly longer in dexmedetomidine group after tourniquet release. Conclusion: We conclude that the addition of 1 mcg/kg of body weight dexmedetomidine or 0.5 mg/kg of body weight ketamine to lignocaine for IVRA improves quality of anesthesia and perioperative analgesia without causing side effects. We considered ketamine reduced the time for onset of block, delayed the onset of tourniquet pain, and reduced postoperative analgesic requirement and had a better patient satisfaction than placebo or dexmedetomidine.